Fostering local adaptation platforms for agriculture: How context specific climate-smart villages (CSVs) can relate to local adaptation efforts. - Vidallo, Rene R.; Bayot, Ruvicyn S.; Rosimo, Magnolia M.; Monville-Oro, Emilita; Gonsalves, Julian Francis; Ilaga, Alicia; Sebastian, Leocadio S.; Manalo, U-Nichols; Baltazar, Perla (International Institute for Rural Reconstruction, 2020)
Local adaptation platforms help empower sub-national and local government players, civil society organizations, and public-private partnerships in demonstrating the validity of agro-ecology-specific solutions to current and future climate change impacts. This brief discusses how Climate-Smart Villages, good examples of local adaptation platform, have served as centers for discovery, adaptation, learning, and sharing of climate-smart agriculture in local communities.